Global uranium market dynamics: analysis and future implications - Sa’d Shannak; Logan Cochrane; Daria Bobarykina (International Journal of Sustainable Energy)
This paper analyzes the global uranium market and assesses whether future supply can meet growing demand through 2050, focusing on market and geopolitical drivers. A dual approach was used, combining econometric analysis and uranium supply curve modeling. The econometric analysis examines the long-term relationship between prices and production volumes, using multiple methods to ensure robustness. Supply curve modeling shows how uranium availability changes with price, which helps gauge market resilience under various conditions. The main finding is a significant gap between projected uranium supply and demand, particularly in medium and high-demand scenarios, with a potential shortage emerging as early as 2035. By 2050, Kazakhstan and Canada are expected to dominate the uranium export market. Political and energy security concerns may lead to new global alliances and trade routes to meet the growing demand for nuclear energy. The study also highlights the International Atomic Energy Agency’s outlook, emphasizing that primary mining will remain the dominant source of uranium, despite contributions from secondary sources. For policymakers, the study stresses the need for strategic interventions, including re-evaluating production and export policies in uranium-rich nations and developing effective strategies to secure supply. Findings offer key insights into market dynamics and ensure nuclear energy's sustainability.